Efektivitas Aplikasi Data Base Kondisi Fisik Atlet Bulu Tangkis Berbasis Android - Titis Pambudi; Siti Baitul Mukarromah; Setya Rahayu; Dody Tri Iwandana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
The purpose of this study was to analyze the effectiveness of the android-based physical conditions of badminton athletes database application. The Research and Development (R&D) method is used in this study to make or develop a product so that it can be used. As a means of evaluating the physical fitness of badminton athletes, this study is developing an Android-based database application. The ADDIE development model, which is a model that includes five stages that include analyze, design, development, implementation, and evaluation, is adapted as part of the research procedure for android application development as a test of the physical condition of badminton athletes. The data analysis technique used is a descriptive percentage to determine the validity of the product from the expert and the response to the acceptance of the expert/expert and coach on the application product for testing the physical condition of badminton athletes through a questionnaire that has been given by the researcher. The research results show that the score of greater than 3.00 is given to the effectiveness value. If the calculated t value is 24.357 greater than t table 2.145, then Ha accepted is declared to be valid and H0 is rejected. The physical fitness application for Android-based badminton athletes has a good percentage of display, language, and media benefits; it has a good percentage of 6.67% with one coach and a good percentage of 93.33 percent with 14 trainers. So it can be concluded that the application for measuring badminton athletes' physical fitness can be developed and used in a good manner. Keywords: Badminton Athletes, Database Application, Effectiveness.